2021
DOI: 10.14710/mkts.v27i2.35783
|View full text |Cite
|
Sign up to set email alerts
|

Wonogiri reservoir operation pattern after the construction of new spillway for flood control

Abstract: Wonogiri reservoir in upstream Bengawan Solo experienced sedimentation problems that endanger its operation. Much of sediments come from Keduang watershed. To overcome this problem, closure dike was constructed to localize the sediment from Keduang watershed. The dike divides the reservoir into main and sediment storage reservoirs, each has its spillway. This paper presents results of the study on Wonogiri Reservoir operation during flood period after dike construction. The study followed a two-step calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
(2 reference statements)
1
6
0
Order By: Relevance
“…The results showed that the T p of the 1982 Design was 13 hours while Pradipta (2014) used 5 hours for all the design flood types. Moreover, Perum Jasa Tirta I (2020) was discovered to have produced 8, 7, and 17-hour for 60-year, 1.2×100-year, and PMF design, respectively while Wijayanti et al (2021) predicted a 5-hour which was similar to the findings of Pradipta (2014) for 1.2×100-year flood and PMF but a 4-hour for the 60-year flood. Meanwhile, the T p obtained for the 60 and 1.2×100-year floods in this study were 4 hours when the rainfall was distributed in a 5-hour duration and but the value changed to 5 hours at a 6-hour duration.…”
Section: The Design Flood For Wonogiri Reservoirsupporting
confidence: 61%
See 3 more Smart Citations
“…The results showed that the T p of the 1982 Design was 13 hours while Pradipta (2014) used 5 hours for all the design flood types. Moreover, Perum Jasa Tirta I (2020) was discovered to have produced 8, 7, and 17-hour for 60-year, 1.2×100-year, and PMF design, respectively while Wijayanti et al (2021) predicted a 5-hour which was similar to the findings of Pradipta (2014) for 1.2×100-year flood and PMF but a 4-hour for the 60-year flood. Meanwhile, the T p obtained for the 60 and 1.2×100-year floods in this study were 4 hours when the rainfall was distributed in a 5-hour duration and but the value changed to 5 hours at a 6-hour duration.…”
Section: The Design Flood For Wonogiri Reservoirsupporting
confidence: 61%
“…The hydrologic model was validated using rainfall-runoff events and data obtained from previous investigations (Nugroho, 2015). The results obtained from this study were also compared to those of previous investigations (Pradipta, 2014;Perum Jasa Tirta I, 2020;Wijayanti et al, 2021).…”
Section: Basin Model Of Flood Hydrograph Simulationmentioning
confidence: 93%
See 2 more Smart Citations
“…Dams are one of the water supply infrastructures both for irrigation and clean water in Indonesia. This dam was built in a location that is calculated to provide maximum storage and is technically safe (Wijayanti et al, 2021;Heydari et al, 2015;Ahmadi et al, 2017;Kartini & Permana, 2016).…”
Section: Dammentioning
confidence: 99%